1996
DOI: 10.1113/jphysiol.1996.sp021735
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric interactions between phosphorylation pathways regulating ciliary beat frequency in human nasal respiratory epithelium in vitro.

Abstract: 1. The effects of the sequential stimulation of ciliary beat frequency (CBF) via two different phosphorylation cascades (dependent on protein kinase A (PKA) and calmodulin, respectively) were determined using video microscopy applied to a perfused preparation of human nasal respiratory epithelium in vitro. Dibutyryl cyclic AMP (db-cAMP) (10-3 M) was used to stimulate PKA and the calcium ionophore 4-Br-A23187 (10-5 M) was used to stimulate calmodulin-dependent phosphorylation.2. Perfusion with db-cAMP (10-3 M) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 28 publications
2
14
0
Order By: Relevance
“…In general, the effects of terbutaline in combination with mannitol on MCC in the present study are in agreement with those observed in in vitro studies of the effects of cAMP and terbutaline combined with a calcium agonist on the CBF in vitro [26,27]. In the present study, the only different finding was that the inhibition observed with terbutaline inhaled before mannitol was transient, lasting only for the duration of the intervention (y20 min).…”
Section: Discussionsupporting
confidence: 92%
“…In general, the effects of terbutaline in combination with mannitol on MCC in the present study are in agreement with those observed in in vitro studies of the effects of cAMP and terbutaline combined with a calcium agonist on the CBF in vitro [26,27]. In the present study, the only different finding was that the inhibition observed with terbutaline inhaled before mannitol was transient, lasting only for the duration of the intervention (y20 min).…”
Section: Discussionsupporting
confidence: 92%
“…al., 2002; Morse et al, 2001;Smith et al, 1996;Tamaoki et al, 1989b;Wyatt et al, 2005;Wyatt et al, 1998). Adrenergic drugs, known to increase CBF (Sanderson and Dirksen, 1989;Wyatt et al, 1998;Yang et al, 1996), also increase intracellular cAMP levels.…”
Section: Discussionmentioning
confidence: 99%
“…Because PKA activation has been tightly linked to stimulation of ciliary motility in many airway cell types (Braiman et al, 1998;Smith et al, 1996;Wyatt et al, 1998a), we next determined if any linkage was present between ethanol activation of PKA activity and ethanol stimulation of CBF. Similar to PKA activation, ethanol, at a concentration threshold of 20 mM, stimulated CBF with maximal stimulation observed at 100 mM (Fig.…”
Section: Ethanol Activation Of Pka Parallels Ethanol Stimulation Of Cmentioning
confidence: 99%